HUBUNGAN STATUS GIZI TERHADAP KEJADIAN INFEKSI SALURAN PERNAPASAN AKUT (ISPA) PADA BALITA DI WILAYAH KERJA PUSKESMAS PAYUNG SEKAKI KOTA PEKANBARU TAHUN 2018 - Aslina, Aslina; Suryani, Indah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2018)
Acute respiratory infections (ISPA) are acute infectious diseases that attack one or more of the respiratory tract from the nose to the lung sac (alveoli) including adnexa tissue such as sinuses/cavity around the nose, middle ear and pleural cavity. One of the factors that influence the incidence of ISPA in children under five is nutritional status. Toddlers with less nutrition will be more susceptible to ISPA even attacks longer than normal child nutrition because of less endurance. The purpose of this study was to determine the relationship of nutritional status to the incidence of acute respiratory infections in infants in the working area of Puskesmas Payung Sekaki Kota Pekanbaru 2018. The reasearch uses quantitative analytic research type, with cross sectional design using questionnaire as a measuring tool as well as sampling in quota sampling. The results of this study indicate that children under five nutritional status with the incidence of acute respiratory infections of 73,2% p value 0,001 OR 4,463(95% CI :1,868-10,663) means there is a relationship between nutritional status of the incidence of ISPA in infants. This research suggestion is expected for parents to provide nutritious food to avoid ARI disease.